Fatigue crack sizing in steel bridge decks using ultrasonic guided waves. (January 2016) - Pahlavan, Lotfollah; Blacquière, Gerrit
Abstract: A baseline-free quantitative sizing methodology utilizing ultrasonic guided waves for fatigue cracks under welded stiffeners in steel bridge decks has been developed. An inverse wavefield extrapolation-based formulation for obtaining the crack reflectivity and depth profile has been presented in the kernel of which, the presence of welded orthogonal stiffeners has been accounted for. Having conducted experiments on a test bridge deck subject to fatigue loading, it has been demonstrated that the crack profile can be estimated from the reflection coefficients obtained. In comparison with the reference measurements, the maximum crack depth estimation error turned out to be about 20%. Highlights: A baseline-free methodology for sizing of fatigue cracks in bridge decks based on guided ultrasonic waves is presented. The increased complexities in the recorded wavefield due to the welded stiffeners are accounted for in the processing. The local crack reflectivity is obtained and translated to crack profile. Limiting the depth and length estimation errors to 20% is shown to be feasible.